Biaxially oriented polypropylene film
The biaxially oriented polypropylene film achieves high rigidity and reduced crater projections in high temperature environments by optimizing surface structure and mechanical properties, resulting in enhanced handling and optical performance.
Patent Information
- Application Number
- JP2024515305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2024-02-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-02-29
AI Technical Summary
Biaxially oriented polypropylene films struggle to maintain high rigidity in high temperature environments while suppressing the formation of steep crater projections, which can lead to optical defects and poor handling.
The biaxially oriented polypropylene film is designed with a specific surface structure characterized by a relatively small actual volume Vmp in the mountain area, a stress F5t value between 50 Pa·m and 1000 Pa·m at 130° C., and controlled surface roughness parameters to achieve both high rigidity and reduced crater projections.
This approach results in a film with excellent quality and handling in high temperature environments, preventing optical defects and ensuring improved mechanical strength and planarity.
Smart Images

Figure 0007658513000004 
Figure 0007658513000001 
Figure 0007658513000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polypropylene film which has excellent quality and handleability in a high-temperature environment and can be suitably used as an industrial material film. [Background technology]
[0002] Biaxially oriented polypropylene films have excellent surface releasability and mechanical properties, and are therefore suitable for use as release films, process films, and support films for a variety of components, including plastic products, building materials, and optical components.
[0003] Biaxially oriented polypropylene films generally form a surface structure having steep protrusions called crater protrusions. Therefore, for example, when an optical film is manufactured using a biaxially oriented polypropylene film as a support, the steep protrusions may be transferred and steep recesses may be formed in the optical film. The optical film is laminated to other members in the next process, and if such steep recesses remain as voids, optical defects will occur, so it has been difficult to use biaxially oriented polypropylene films as supports for high-end optical films.
[0004] In addition, the resin composition for obtaining the optical film is coated on the surface of the biaxially oriented polypropylene film, and then dried and cured in a high-temperature oven. Therefore, the biaxially oriented polypropylene film needs to maintain high rigidity even in a high-temperature environment. In order to maintain high rigidity in a high-temperature environment, it is generally necessary to use a highly crystalline polypropylene resin as the raw material for the biaxially oriented polypropylene film, but it is known that when a highly crystalline polypropylene raw material is used, the above-mentioned crater protrusions are easily formed on the surface. In this way, there is a trade-off between achieving high rigidity at high temperatures and suppressing the crater protrusion structure, and it has been very difficult to achieve both at the same time.
[0005] Thus, the support film of the optical film is required to suppress the formation of a steep protrusion structure while having high rigidity in a high-temperature environment. For example, Patent Documents 1 and 2 describe examples in which a copolymer or a low-crystalline polypropylene raw material is blended with a propylene-based resin as the main raw material. Patent Document 3 describes an example in which a crystal nucleating agent is added to improve mechanical strength at high temperatures and the film is highly crystallized. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-107612 A [Patent Document 2] International Publication No. 2022 / 075101 [Patent Document 3] JP 2008-050393 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the method of blending a copolymer or a low-crystalline polypropylene raw material with the propylene-based resin as the main raw material described in Patent Documents 1 and 2, the crystallinity of the substrate is likely to decrease. Therefore, the obtained film has low rigidity in a high-temperature environment, and there is a concern that wrinkles will occur and flatness will deteriorate in a high-temperature environment, which is problematic in terms of impairing the quality and handleability in a high-temperature environment. In addition, in the method described in Patent Document 3, the crystallinity of the film surface is high, and a steep protrusion structure is likely to be formed. Therefore, when the obtained film is used as a support film, there is a concern that defects will occur, and there is a problem in that the quality will deteriorate. Therefore, the present invention aims to solve the above problems and provide a biaxially oriented polypropylene film that is excellent in quality and handleability in a high-temperature environment. [Means for solving the problem]
[0008] In order to solve the above-mentioned problems, the biaxially oriented polypropylene film of the present invention has the following configuration. That is, the biaxially oriented polypropylene film of the present invention has a relatively small peak actual volume Vmp and a peak actual volume Vmp of 0.1 μL / m 2 More than 50μL / m 2 The biaxially oriented polypropylene film is characterized in that, when the side that is equal to or less than the above is defined as side A, one side is said side A, and the value F5t obtained by multiplying the stress F5 value at 5% elongation in the direction perpendicular to the main orientation of the film at 130°C by the film thickness is 50 Pa·m or more and 1000 Pa·m or less. Effect of the Invention
[0009] According to the present invention, it is possible to provide a biaxially oriented polypropylene film having excellent quality and handleability in a high-temperature environment. [Brief description of the drawings]
[0010] [Figure 1] 1 is a conceptual diagram showing a peak actual volume Vmp and a valley volume Vvv. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The biaxially oriented polypropylene film of the present invention has a relatively small peak actual volume Vmp of 0.1 μL / m 2 More than 50μL / m 2 When the surface which is equal to or less than or equal to side A is defined as side A, one side is side A, and the value F5t obtained by multiplying the stress F5 value at 5% elongation in the direction perpendicular to the main orientation of the film at 130°C by the film thickness is 50 Pa·m or more and 1000 Pa·m or less. The biaxially oriented polypropylene film of the present invention will be described in detail below.
[0012] The peak actual volume Vmp (hereinafter sometimes simply referred to as Vmp) is one of the surface parameters obtained from a scanning white light interference microscope. More specifically, as shown in Fig. 1, the peak actual volume Vmp (symbol 1) can be expressed as the area surrounded by a load curve (symbol 2) with the vertical axis representing height and the horizontal axis representing the areal load ratio, an equivalent line (symbol 3) at an areal load ratio of 10%, and a position line (vertical axis) representing the areal load ratio of 0%.
[0013] Biaxially oriented polypropylene films are prone to forming steep protrusion structures called crater protrusions. Therefore, for example, when a biaxially oriented polypropylene film is used as a support and an optical film is formed on the surface thereof, the steep protrusions may be transferred to form steep recesses in the optical film. If such recesses are transferred to the optical film, the recesses remain as voids when the optical film is bonded to another member in the next process, which may cause optical defects.
[0014] There are various parameters that represent surface roughness, but for example, the average surface roughness Sa, maximum height Sz, maximum projection height Sp, etc., do not show a high correlation with the height or frequency of the steep projection structure. The inventors have found that Vmp, which represents the volume of the protruding peaks, becomes large when the number of steep projections is large or the height of the steep projections is high, that is, Vmp is particularly highly correlated with the steep projection structure. In the biaxially stretched propylene film of the present invention, it is important to control Vmp within an appropriate range in order to solve the problems described below. In addition, when the difference in Vmp between both sides is 0.1 μL / m 2 If this is the case, it is considered that there is a difference in Vmp between the two sides, and "the side with a relatively small peak actual volume Vmp" refers to the side with the relatively lower Vmp of the two sides of the biaxially oriented polypropylene film when there is a difference in Vmp between the two sides.
[0015] From the viewpoint of achieving both quality and ease of handling at high temperatures, the biaxially oriented polypropylene film of the present invention has a relatively small peak actual volume Vmp and a peak actual volume Vmp of 0.1 μL / m 2 More than 50μL / m 2It is important that one of the surfaces is surface A, where the surface is defined as surface A. From the above viewpoint, the upper limit of Vmp on surface A is preferably 30 μL / m 2 , more preferably 10 μL / m 2 Vmp is 50μL / m 2 A larger value means that many steep projection structures are formed on the surface of the biaxially oriented polypropylene film. Therefore, when the biaxially oriented polypropylene film is used as a support film for an optical film, if an optical film is formed on such a surface, the projection structures may be transferred to the surface of the optical film, resulting in a deterioration in quality. From the above viewpoint, the lower limit of Vmp on the A side is preferably 0.3 μL / m 2 , more preferably 0.5 μL / m 2 Vmp is 0.1μL / m 2 A smaller value means that the surface of the biaxially oriented polypropylene film is excessively smooth. Therefore, a biaxially oriented polypropylene film having such a surface may be wrinkled due to an increased dynamic friction coefficient during transport in a high-temperature environment or immediately after heating.
[0016] To obtain a biaxially stretched polypropylene film having an A-side, for example, a method can be used in which the raw material composition of the biaxially stretched polypropylene film is within the range described below, and the film-forming conditions are within the range described below. In particular, it is effective to use an olefin-based elastomer resin having a softening temperature within an appropriate range, which is uniformly dispersed by melt-kneading it with a polypropylene resin in advance to form chips, as the raw material for the outermost layer, and to use a polypropylene resin having a half crystallization time and melting point within an appropriate range as the main component of the outermost layer (details will be described later). In addition, in terms of the film-forming process, it is effective to set the casting temperature to a low temperature to optimize the crystallization rate during casting, suppress the formation of β-crystal spherulites, and form a dense spherulite structure, and to set the preheating temperature and stretching temperature during longitudinal stretching and transverse stretching within the appropriate range described below, and precisely control the surface structure by controlling the deformation of the elastomer resin domain. These methods can also be used in combination as appropriate.
[0017] In the biaxially stretched polypropylene film of the present invention, from the viewpoint of improving the handling property and quality at high temperatures, the value F5t obtained by multiplying the stress F5 value at 5% elongation in the direction perpendicular to the main orientation of the film at 130°C by the film thickness is 50 Pa·m or more and 1000 Pa·m or less. From the above viewpoint, the lower limit of F5t is preferably 100 Pa·m, more preferably 150 Pa·m. If F5t is less than 50 Pa·m, when a resin composition that is a raw material for an optical film or the like is applied onto the biaxially stretched polypropylene film and then dried and cured in a high-temperature oven, the biaxially stretched polypropylene film stretches in the longitudinal direction and shrinks in the width direction. As a result, the flatness of the biaxially stretched polypropylene film is impaired, and there is a concern that the quality and handling property will deteriorate. From the viewpoint of feasibility, the upper limit of F5t is 1000 Pa·m, preferably 400 Pa·m, and more preferably 300 Pa·m.
[0018] In order to suppress deformation under high temperature and high tension environments, it is useful to increase the thickness of the biaxially oriented polypropylene film in addition to maintaining high mechanical strength in the low elongation range even in high temperature environments, and it was found that the degree of deformation under high temperature and high tension environments is strongly correlated with the value of F5t. However, when making the biaxially oriented polypropylene film thicker, the cooling efficiency decreases during the process of obtaining a cast film by melt extrusion, and many β-crystal spherulites are formed in the cast film. The presence of such β-spherulites causes crater protrusions after biaxial stretching, so there is a trade-off between thickening the biaxially oriented polypropylene film and Vmp, and it was previously difficult to achieve both at the same time.
[0019] Here, the main orientation direction refers to the direction that shows the highest value when the Young's modulus is measured in each direction that forms an angle of 0° to 165° with respect to an arbitrary direction in the film plane, with the arbitrary direction being set as 0°. The direction perpendicular to the main orientation refers to the direction perpendicular to the main orientation direction in the film plane. The Young's modulus here refers to the Young's modulus calculated in accordance with the method specified in JIS K 7161 (2014) by setting a rectangular sample with a length of 150 mm (measurement direction) x width of 10 mm at an initial chuck distance of 50 mm and performing a tensile test at room temperature at a tensile speed of 300 mm / min. The details of the method for measuring the Young's modulus will be described later.
[0020] However, in cases where it is impossible to obtain a sample of the above size and therefore impossible to measure and calculate Young's modulus by the above method, the crystal orientation of the polypropylene α-crystal (110) plane of the biaxially stretched polyolefin film can be measured using wide-angle X-rays as follows, and the main orientation direction can be determined based on the following criteria: That is, X-rays (CuKα rays) are incident perpendicularly to the film surface, and the crystal peak at 2θ = approximately 14° (α-crystal (110) plane) is scanned in the circumferential direction to obtain a diffraction intensity distribution. The direction with the highest diffraction intensity is determined as the main orientation direction, and the direction perpendicular to this in the film plane is determined as the direction perpendicular to the main orientation direction.
[0021] The F5t of a biaxially stretched polypropylene film can be measured by the following procedure. First, the biaxially stretched polypropylene film is heated for 1 minute in an oven heated to 130°C, and then a tensile test is performed at a tensile speed of 300 mm / min to measure the load applied to the film when the elongation of the biaxially stretched polypropylene film is 5%. The value obtained by dividing the value by the cross-sectional area (film thickness x width) of the sample before the test is calculated as the stress at an elongation of 5%, and this is multiplied by the film thickness to measure and calculate. The measurement method will be described in detail later.
[0022] In order to set F5t within the above range, for example, a method can be used in which the raw material composition of the biaxially stretched polypropylene film is set to the range described below, and the film-forming conditions are set to the range described below. In particular, it is effective to optimize the crystallinity and orientation of the film by using a polypropylene resin having a melting point and molecular weight in an appropriate range as the main component. In addition, in terms of the film-forming process, the preheating temperature and stretching temperature during transverse stretching can be set to the melting point of the main component polypropylene resin or lower, and a relaxation treatment of 2.0% or more and less than 10%, preferably 3.0% or more and less than 10%, can be performed after longitudinal stretching, thereby enabling transverse stretching without significantly relaxing the oriented structure of the uniaxially stretched film after longitudinal stretching, and it is effective in maintaining high mechanical strength even at high temperatures. These methods can also be used in combination as appropriate.
[0023] In the biaxially oriented polypropylene film of the present invention, from the viewpoint of improving the handling property in the transport and winding process after high-temperature processing and further improving the quality, the dynamic friction coefficient μd of the front and back of the film after heating at 130 ° C for 10 minutes is preferably 0.30 or more and 1.40 or less. From the above viewpoint, the upper limit of the dynamic friction coefficient μd of the front and back of the film after heating at 130 ° C for 10 minutes is more preferably 1.20, even more preferably 1.00, particularly preferably 0.80, and most preferably 0.75. On the other hand, the lower limit of the dynamic friction coefficient μd of the front and back of the film after heating at 130 ° C for 10 minutes is not particularly limited, but is substantially about 0.30. Here, the "dynamic friction coefficient μd of the front and back of the film" is the friction coefficient measured by overlapping and rubbing different surfaces against each other, and the dynamic friction coefficient μd can be measured in accordance with JIS K 7125 (1999) (details will be described later).
[0024] In the biaxially oriented polypropylene film of the present invention, the olefin-based elastomer resin may be uniformly dispersed in order to suppress the formation of crater protrusions. In such an embodiment, the olefin-based elastomer may soften when heated to 130°C, resulting in an increase in the coefficient of friction between the front and back of the film, which may result in poor flatness after heating. In other words, there is a trade-off between smoothing the film surface and making it easy to slip after high-temperature heating, and it is difficult to achieve both at the same time.
[0025] In order to set the dynamic friction coefficient μd between the front and back of the film in the above-mentioned preferred range after heating at 130°C for 10 minutes, for example, a method can be used in which the raw material composition of the biaxially oriented polypropylene film is set in the range described below, and the film-forming conditions are set in the range described below. In particular, it is effective to suppress the softening of the elastomer resin when heated at 130°C by setting the softening temperature and the amount of addition of the olefin-based elastomer resin in the appropriate range. In addition, in terms of the film-forming process, it is also effective to set the preheating temperature and stretching temperature of the longitudinal stretching and transverse stretching in the appropriate range, and to perform a relaxation treatment in the longitudinal direction of the uniaxially stretched film after longitudinal stretching in a temperature range below the softening temperature of the elastomer to form a fine uneven structure on the film surface, thereby reducing the contact area between the transport roll and the film surface. These methods can be used in combination as appropriate.
[0026] In the biaxially oriented polypropylene film of the present invention, from the viewpoint of quality, when the side opposite to the side A is side B, the side B is 1 mm 2 The number of craters with a major axis exceeding 100 μm is 0.001 / mm 2 More than 30 pieces / mm 2 The number of craters with a major axis exceeding 100 μm is preferably 30 / mm 2 If the number is larger, when the biaxially oriented polypropylene film is used as a support for manufacturing an optical film, the steep protrusions originating from the craters on side B may be transferred to the optical film when the optical film is formed on side A and wound up, and steep recesses may be formed in the optical film. When such an optical film is laminated to another member in the next process, the steep recesses may remain as voids, which may cause optical defects. From the above viewpoint, the fewer the number of craters, the better, and the upper limit is more preferably 20 craters / mm. 2 , and more preferably 10 pieces / mm 2 , and most preferably 5.0 pieces / mm 2 The lower limit is not particularly limited, but is substantially 0.001 pieces / mm 2In the present invention, the term "crater" refers to a shape having a large depression, specifically, a depression with a major axis of 150 nm or more when the height threshold is set to -0.1 μm. 2 The number of craters per unit area can be measured using a scanning white light interference microscope and an associated analysis system, and the details of the measurement method will be shown in the Examples.
[0027] B side 1mm 2 In order to keep the number of craters with major axes exceeding 100 μm per unit area within the above range, for example, a method can be used in which the raw material composition of the biaxially oriented polypropylene film is within the range described below, and the film-forming conditions are within the range described below. Specifically, in addition to the method of obtaining a biaxially oriented polypropylene film having an A-side, it is preferable to lower the air temperature of the air knife, optimize the blown air speed, and optimize the thickness of the film, from the viewpoint of efficiently cooling the non-cooled drum surface of the sheet on the casting drum. Note that the preferred conditions for the temperature and speed of the air from the air knife will be described later.
[0028] In the biaxially oriented polypropylene film of the present invention, in order to improve the handling property, the peak density Spd of the A-side is 1.0 peaks / mm 2 More than 100 pieces / mm 2 It is preferable that the peak density Spd is 100% or less. Hereinafter, the peak density Spd may be simply referred to as Spd. The biaxially oriented polypropylene film of the present invention is prone to deterioration in slipperiness because the generation of crater protrusions is suppressed, but in order to maintain good slipperiness even on such a surface and obtain a film with good flatness, it is preferable to form many fine uneven structures on the film surface.
[0029] From the above viewpoint, the lower limit of Spd of the A side is preferably 2.0 pieces / mm 2 , more preferably 5.0 pieces / mm 2 The Spd of the A side is 1.0 pieces / mm 2By setting the value to the above value, the slipperiness of the biaxially oriented polypropylene film is maintained, so that the occurrence of wrinkles during transportation and the associated deterioration of flatness can be reduced. From the above viewpoint, the upper limit of Spd of the A side is preferably 60 pieces / mm 2 , more preferably 40 pieces / mm 2 and particularly preferably 20 pieces / mm 2 and most preferably 17 pieces / mm 2 The Spd of the A side is 100 pieces / mm 2 By satisfying the above condition, the surface roughness of the biaxially oriented polypropylene film is appropriately suppressed from being finely textured, and therefore, when the film is used as an industrial material film, the deterioration of the handleability due to the non-smoothness is reduced. Spd can be measured using a scanning white light interference microscope and an associated analysis system, and the details of the measurement method are shown in the Examples.
[0030] In order to set the Spd of the A side within the above range, for example, a method can be used in which the raw material composition of the biaxially stretched polypropylene film is set within the range described below, and the film-forming conditions are set within the range described below. In particular, it is effective to melt-knead an olefin-based elastomer resin having a softening temperature within an appropriate range in advance to uniformly disperse it in the polypropylene resin. In addition, in terms of the film-forming process, it is also effective to set the preheating temperature and stretching temperature for longitudinal stretching and transverse stretching within an appropriate range, and to subject the film after longitudinal stretching to a relaxation treatment in the longitudinal direction at a temperature range below the softening temperature of the elastomer to form a fine uneven structure on the film surface, thereby reducing the contact area between the transport roll and the film surface. These methods can be used in combination as appropriate.
[0031] When the biaxially oriented polypropylene film of the present invention is used as a protective film, from the viewpoint of maintaining the flatness and quality of the adherend, the valley volume Vvv of the A side is set to 2.0 μL / m 2 More than 20μL / m 2It is preferable that the valley volume Vvv (hereinafter, sometimes simply referred to as Vvv) is one of the surface parameters obtained by measurement using a scanning white light interference microscope. More specifically, as shown in FIG. 1, the valley volume Vvv (reference number 4) can be expressed as a portion surrounded by a load curve (reference number 2) in which the vertical axis is height and the horizontal axis is the load area ratio, an equivalent line (reference number 5) at a load area ratio of 80%, and a position line (reference number 6) at a load area ratio of 100%. Vvv represents the volume of the space of the protruding valley, and a small Vvv on the surface means that the surface of the biaxially oriented polypropylene film tends to have fewer coarse recessed structures. Vvv can be measured using a scanning white light interference microscope and an associated analysis system, and the details of the measurement method are shown in the examples.
[0032] In general biaxially stretched polypropylene films for industrial use, methods for controlling convex portions are often used, but concave portions are rarely intentionally controlled. On the other hand, in the manufacturing process of biaxially stretched polypropylene films, coarse spherulite structures such as β crystals formed during the crystallization process are stretched, and coarse concave portions such as craters are easily formed. When an optical film is formed using a biaxially stretched polypropylene film having such concave portions as a support, air pockets may be generated in the coarse concave portions and deformation of the surface of the mating member may occur. Therefore, in order to solve the problems of smoothness and handleability, it is preferable that the valley volume Vvv of the biaxially stretched polypropylene film of the present invention is controlled to an appropriate range.
[0033] From the above viewpoint, the lower limit of Vvv of the A side is more preferably 2.5 μL / m 2 , and more preferably 3.0 μL / m 2 The Vvv of the A side is 2.0 μL / m 2 By satisfying the above, the biaxially oriented polypropylene film has appropriate slipperiness and good handling properties. From the above viewpoint, the upper limit of Vvv of the A side is more preferably 15 μL / m 2 , and more preferably 10 μL / m 2 and particularly preferably 7.0 μL / m 2and most preferably 5.0 μL / m 2 The Vvv of the A side is 20 μL / m 2 By keeping Vvv of surface A at 2.0 μL / m or less, the number of large concave portions on the surface is reduced, which makes it possible to suppress an increase in air pocket defects and deterioration of flatness of the optical film formed on surface A, thereby improving the quality. 2 More than 20μL / m 2 The biaxially oriented polypropylene film described below has good handling properties and smoothness, and can be suitably used, for example, as an industrial material film for producing optical films.
[0034] In order to set Vvv within the above range, for example, a method can be used in which the raw material composition of the biaxially stretched polypropylene film is set within the range described below, and the film-forming conditions are set within the range described below. In particular, it is effective to add an elastomer resin having a softening temperature within an appropriate range to a polypropylene resin having a crystallization rate within an appropriate range to make the spherulites formed during casting finer, to lower the temperature of the casting drum to increase the cooling efficiency during casting, to set the preheating and stretching temperature within an appropriate range, and to stretch uniformly while suppressing the formation of coarse irregularities. In particular, it is effective to perform a relaxation treatment of 2.0% or more and less than 10%, preferably 3.0% or more and less than 10%, after longitudinal stretching, or to set the temperature in the preheating and stretching process during transverse stretching to a temperature higher than the softening temperature of the elastomer resin added to the film and lower than the melting point of the polypropylene resin most abundant in the film, and to stretch in the width direction while maintaining the dense irregular structure formed on the uniaxially stretched film. These methods can also be used in combination as appropriate.
[0035] From the viewpoint of flatness, the biaxially stretched polypropylene film of the present invention preferably has a thickness of 10 μm or more and 100 μm or less. From the above viewpoint, the lower limit of the thickness is preferably 10 μm, more preferably 15 μm. When the biaxially stretched polypropylene film is used as an industrial material film, the mechanical strength is ensured, so that the occurrence of wrinkles is reduced, and the flatness is improved, and the handling property is improved. From the above viewpoint, the upper limit of the thickness is preferably 100 μm, more preferably 50 μm, even more preferably 40 μm, and most preferably 28 μm. When the thickness is 100 μm or less, cooling proceeds efficiently during casting, so that the flatness is improved. The thickness of the biaxially stretched polypropylene film can be adjusted by the screw rotation speed of the extruder, the thickness and width of the unstretched sheet, the film-forming speed, the stretching ratio, and the like. The thickness of the biaxially stretched polypropylene film can be measured with a micro thickness meter, and the detailed measurement method will be described later.
[0036] From the viewpoint of improving blocking resistance, the biaxially oriented polypropylene film of the present invention is preferably such that the heat of fusion at 160°C or less is 5% or more and 50% or less of the total heat of fusion when the film is heated from 30°C to 260°C by a differential scanning calorimeter DSC. Hereinafter, the "heat of fusion at 160°C or less of the total heat of fusion" may be referred to as the ratio of the heat of fusion at 160°C or less. From the above viewpoint, the ratio of the heat of fusion at 160°C or less is more preferably 45% or less, and even more preferably 40% or less. By making the ratio of the heat of fusion at 160°C or less 50% or less, the amount of low-melting point components that are likely to cause deformation or fusion during long-term storage in an oven during heating or in a wound state is suppressed, thereby reducing the occurrence of slippage and blocking. In addition, the lower limit of the ratio of the heat of fusion at 160°C or less is more preferably 8%, and even more preferably 13%. By making the proportion of heat of fusion at 160° C. or less 5% or more, film rupture during transverse stretching is suppressed, making it possible to perform stretching more stably.
[0037] In consideration of the above, in order to set the ratio of the heat of fusion at 160°C or less within the above range, for example, it is effective to set the raw material composition of the biaxially stretched polypropylene film to the range described below, and to set the film-forming conditions to the range described below. In particular, it is effective to optimize the crystallinity and orientation of the biaxially stretched polypropylene film by using a polypropylene resin having a melting point, molecular weight, and half-crystallization time in an appropriate range as the main component. In addition, in terms of the film-forming process, it is effective to set the preheating temperature and stretching temperature during transverse stretching to be equal to or lower than the melting point of the polypropylene resin, which is the main component. By setting such conditions, transverse stretching is possible without significantly relaxing the orientation structure of the uniaxially stretched film after longitudinal stretching, and a biaxially stretched polypropylene film having a more stable crystal structure is obtained. In addition, these methods can be used in combination as appropriate.
[0038] Next, resins that can be used in the biaxially oriented polypropylene film of the present invention will be described, but the resins are not necessarily limited thereto.
[0039] The biaxially oriented polypropylene film of the present invention is mainly composed of polypropylene resin. In the present invention, the term "main component" means a component whose proportion in the total components of the film is more than 50% by mass and not more than 100% by mass. The lower limit of the proportion of the polypropylene resin in the total components of the film is more preferably 70% by mass, even more preferably 80% by mass, and particularly preferably 90% by mass. The biaxially oriented polypropylene film of the present invention may contain only one type of polypropylene resin, but may also contain two or more types of polypropylene resin. In addition, when two or more types of components corresponding to polypropylene resin are contained in the film, if the total of these components is more than 50% by mass and not more than 100% by mass, it is considered that the film is "mainly composed of polypropylene resin". In addition, in the present invention, the term "polypropylene resin" refers to a resin that contains more than 50 mol% and not more than 100 mol% of propylene units when the total structural units constituting the molecular chain of the resin are 100 mol%.
[0040] The biaxially oriented polypropylene film of the present invention is not particularly limited in terms of its layer structure, and may have either a single layer or a laminate structure. However, from the viewpoint of satisfying different properties such as smoothness, rigidity, and handleability, it is preferable that the film is composed of at least two layers, and it is particularly preferable that the film has a surface layer (I) and a base layer (II).
[0041] When the biaxially oriented polypropylene film of the present invention has a laminated structure, from the viewpoints of handleability at high temperatures and quality, it is preferable that a layer containing a polypropylene resin having a melting point of 155° C. or more and 175° C. or less (preferably 160° C. or more and 175° C. or less) and an elastomer resin having a softening temperature of 70° C. or more and 150° C. or less is located as the outermost layer on at least one side. For example, in the case of a biaxially oriented polypropylene film having a surface layer (I) and a base layer (II) as described above, the surface layer (I) is the outermost layer.
[0042] The polypropylene resin (polypropylene resin A) that is most preferably contained in the polypropylene film of the present invention will be described below. The weight average molecular weight Mw of polypropylene resin A is 20×10 4 More than 60×10 4 From the viewpoints of crystallization behavior and F5t, which is the value obtained by multiplying the stress F5 value at 5% elongation in the direction perpendicular to the main orientation of the obtained biaxially stretched polypropylene film at 130° C. by the film thickness, it is preferable that the lower limit of Mw is 25×10 or less. 4 , and more preferably 30×10 4 and the upper limit of Mw is more preferably 45×10 4 , and more preferably 40×10 4 In order to set the Mw of the polypropylene resin to the above value, it is preferable to adopt a method of adjusting the hydrogen gas concentration during polymerization, or to appropriately select a catalyst and / or a co-catalyst and a composition.
[0043] The lower limit of the melting point of polypropylene resin A is preferably 155 ° C, more preferably 158 ° C, even more preferably 160 ° C, and particularly preferably 163 ° C. When the melting point of the polypropylene resin is 155 ° C or more, the obtained biaxially oriented polypropylene film has excellent heat resistance, and when used as a release film or a process film for manufacturing an optical film, for example, it can maintain its shape even when passing through a process in which heat is applied after being laminated with an adherend, and deformation of the adherend can be suppressed. The upper limit of the melting point of polypropylene resin A is preferably 170 ° C, more preferably 168 ° C, and even more preferably 165 ° C. By having a melting point of the polypropylene resin of the present invention of 170 ° C or less, the crystal formation rate is appropriately suppressed, so that the formation of a coarse uneven structure during crystallization by casting is suppressed, and the smoothness of the biaxially oriented polypropylene film is good, and the dynamic friction coefficient μd of the front and back of the film after heating at 130 ° C for 10 minutes can be easily controlled within a suitable range.
[0044] The polypropylene resin A is preferably a homopolypropylene resin from the viewpoints of excellent heat resistance, good mechanical properties and lubricity even in a high-temperature environment, and good handleability.
[0045] The polypropylene resin A is not particularly limited as long as it satisfies the above-mentioned preferred conditions, but examples of polypropylene resins that can be suitably used in the biaxially oriented polypropylene film of the present invention and are commercially available include polypropylene resins E-203GP and F113G manufactured by Prime Polymer Co., Ltd., polypropylene resins D101, FS2011DG3, and FSX20L8 manufactured by Sumitomo Chemical Co., Ltd., and polypropylene resins FY6H and FL4 manufactured by Japan Polypropylene Corporation.
[0046] When the biaxially oriented polypropylene film of the present invention has a laminated structure, the polypropylene resin (polypropylene resin B) that is most preferably contained in the outermost layer on the A-side side will be described. The lower limit of the half crystallization time of polypropylene resin B is preferably 50 seconds, more preferably 100 seconds, even more preferably 200 seconds, particularly preferably 300 seconds, and most preferably 400 seconds. When the half crystallization time of the polypropylene resin is 50 seconds or more, crystal formation is appropriately suppressed and coarse structures are less likely to be formed during crystallization by casting, improving the smoothness of the biaxially oriented polypropylene film, and making it easier to control the dynamic friction coefficient μd of the front and back of the film after heating at 130 ° C. for 10 minutes within a suitable range. In addition, the upper limit of the half crystallization time is preferably 1500 seconds or less, more preferably 1000 seconds or less. By setting the half crystallization time to 1500 seconds or less, crystal formation becomes sufficient, and fine unevenness is easily formed on the film surface. Therefore, the biaxially oriented polypropylene film becomes easy to slip and has good handleability.
[0047] The half-crystallization time of polypropylene resin B is an index of the crystallization rate determined by isothermal crystallization measurement at 130°C using DSC. The crystallization rate is determined by a combination of factors such as stereoregularity, crystallinity, and molecular weight. The detailed method and device for measuring the half-crystallization time of polypropylene resin will be described in the Examples section below.
[0048] The upper limit of the melting point of polypropylene resin B is preferably 175°C, more preferably 170°C, even more preferably 168°C, and particularly preferably 165°C. By having the melting point of the polypropylene resin of the present invention be 175°C or less, the affinity with the elastomer resin is improved, and the spherulite structure formed during casting can be refined, and as a result, the formation of steep protrusions derived from craters can be suppressed. The lower limit of the melting point of polypropylene resin B is preferably 155°C, more preferably 158°C, and even more preferably 160°C. By having the melting point of the polypropylene resin be 155°C or more, the transparency of the film can be easily maintained even under conditions of high transverse stretching temperature.
[0049] The polypropylene resin B is not particularly limited as long as it satisfies the above-mentioned preferable conditions, but examples of polypropylene resins that can be used in the biaxially stretched polypropylene film of the present invention and are commercially available include, in addition to the polypropylene resins A listed above, polypropylene resins E-200GP, E-203GP, and Y-400GP manufactured by Prime Polymer Co., Ltd., polypropylene resins WF836DG3 manufactured by Sumitomo Chemical Co., Ltd., polypropylene resins FY6H, MA3U, and SA4L manufactured by Japan Polypropylene Co., Ltd., and polypropylene resin VS700A manufactured by Sun Allomer Co., Ltd. In addition, there are polypropylene resins that have both the characteristics that are preferably possessed by the above-mentioned polypropylene resin A and the characteristics that are preferably possessed by the polypropylene resin B. These can be suitably used for both polypropylene resins A and B, and the same polypropylene resin can be used as polypropylene resins A and B.
[0050] The biaxially stretched polypropylene film of the present invention may contain, in addition to the above-mentioned polypropylene resin, a polypropylene resin containing a copolymerization component with other unsaturated hydrocarbons within a range that does not impair the effects of the present invention (hereinafter, sometimes referred to as a copolymerized polypropylene resin). Examples of monomer components constituting the copolymerization components in the copolymerized polypropylene resin include ethylene, 1-butene, 1-pentene, 3-methylpentene-1, 3-methylbutene-1, 1-hexene, 4-methylpentene-1, 5-ethylhexene-1, 1-octene, 1-decene, 1-dodecene, vinylcyclohexene, styrene, allylbenzene, cyclopentene, norbornene, and 5-methyl-2-norbornene. From the viewpoint of dimensional stability of the obtained biaxially stretched polypropylene film, the copolymerization amount of the copolymerized polypropylene resin is preferably less than 10 mol% when the total constituent units constituting the resin are 100 mol%.
[0051] When the copolymerized polypropylene resin contains ethylene as a copolymerization component, the content of the ethylene component is preferably 10 mol% or less. More preferably, it is 5 mol% or less, and even more preferably, it is 3 mol% or less. The higher the content of the ethylene component, the lower the crystallinity and the easier it is to improve the transparency, but if the content of the ethylene component exceeds 10 mol%, the strength of the biaxially oriented polypropylene film may decrease, or the heat resistance may decrease, resulting in a worsening of the heat shrinkage rate. In addition, the resin may be easily deteriorated during the extrusion process, and fish eyes may easily occur in the obtained biaxially oriented polypropylene film.
[0052] The biaxially stretched polypropylene film of the present invention preferably contains an elastomer resin, which is a polyolefin resin different from the above-mentioned polypropylene resin. By adding and dispersing the elastomer resin in the above-mentioned polypropylene resin, it becomes easier to promote the structure refinement during casting or stretching.
[0053] From the viewpoints of dispersibility in polypropylene resin and the effect of miniaturizing the structure formed by the polypropylene resin, the elastomer resin is preferably an olefin-based elastomer, and more preferably a propylene-based elastomer.
[0054] From the viewpoint of dispersibility in polypropylene resin, the MFR of the elastomer resin is preferably 3.0 g / 10 min or more and 50 g / 10 min or less, the lower limit is more preferably 5.0 g / 10 min, the upper limit is more preferably 40 g / 10 min, further preferably 10 g / 10 min, and most preferably 8.0 g / 10 min. The MFR can be measured in accordance with JIS K7210-1 (2014).
[0055] The softening temperature of the elastomer resin is preferably 70°C or higher and 150°C or lower. From the viewpoint described later, the lower limit of the softening temperature of the elastomer resin is more preferably 110°C, and even more preferably 117°C. The upper limit of the softening temperature of the elastomer resin is more preferably 140°C, even more preferably 130°C, and particularly preferably 123°C. When the softening temperature of the elastomer resin is 70°C or higher, the biaxially oriented polypropylene film may be blocked when it is stored for a long period of time in a high temperature environment in summer, for example, in a rolled state. When the softening temperature of the elastomer resin is 150°C or lower, it is easy to control the deformation of the elastomer resin during the stretching process, so that the formation of a fine uneven surface structure is promoted and the formation of a coarse protrusion structure can be suppressed, and as a result, the flatness and transfer suppression effect of the biaxially oriented polypropylene film are improved. The softening temperature of the elastomer resin can be measured in accordance with JIS K 7196 (1991), and the details will be described later.
[0056] In the biaxially stretched polypropylene film of the present invention, when the total of the polypropylene resin and the elastomer resin in the outermost layer on the A-side side is taken as 100% by mass, the proportions of the polypropylene resin and the elastomer resin in the layer are preferably as shown below. The lower limit of the proportion of the polypropylene resin in the outermost layer is preferably 50% by mass, more preferably 60% by mass, even more preferably 65% by mass, and particularly preferably 70% by mass. The upper limit of the proportion of the polypropylene resin in the outermost layer is preferably 99% by mass, more preferably 90% by mass, and even more preferably 80% by mass. The lower limit of the proportion of the elastomer resin in the outermost layer is preferably 1% by mass, more preferably 10% by mass, and even more preferably 20% by mass. The upper limit of the proportion of the elastomer resin in the outermost layer is preferably 50% by mass, more preferably 40% by mass, even more preferably 35% by mass, and particularly preferably 30% by mass. When the proportion of the elastomer resin relative to the total amount of resin components in the outermost layer on the A-side is 50% by mass or less, loss of surface flexibility after the biaxially oriented polypropylene film is heated in an oven, etc. is reduced, and blocking between the biaxially oriented polypropylene films when rolled is also reduced. On the other hand, when the proportion of the elastomer resin relative to the total amount of resin components in the outermost layer on the A-side is 1% by mass or more, it becomes easy to adjust the Vmp of side A and the dynamic friction coefficient μd of the front and back of the film after heating at 130°C for 10 minutes, etc., to the preferred ranges described above.
[0057] Elastomer resins are generally used as raw materials for heat seal layers, and there is a high possibility that the biaxially oriented polypropylene film will lose its slipperiness or cause blocking when heated, so it has not been common to use elastomer resins in the outermost layer of a film used as a protective film or support film. The biaxially oriented polypropylene film of the present invention can be used even in high temperature environments by selecting and controlling the melting point, temperature, and amount of the elastomer resin to be added within the above-mentioned appropriate ranges.
[0058] The elastomer resin can be appropriately selected with reference to the above MFR, melting point, and softening temperature. Examples of commercially available elastomer resins that can be used in the biaxially oriented polypropylene film of the present invention include, but are not limited to, "Tafmer" (registered trademark) "PN2060", "PN2070", and "BL3450" manufactured by Mitsui Chemicals, Inc., "Wintec" (registered trademark) "WMG30" manufactured by Japan Polypropylene Corporation, "Dynaron" (registered trademark) "2324P" manufactured by JSR Corporation, and "Milastomer" (registered trademark) "8030NHS" manufactured by Mitsui Chemicals, Inc.
[0059] The polypropylene resin and elastomer resin used in the biaxially oriented polypropylene film of the present invention may contain various additives, such as a crystal nucleating agent, an antioxidant, a heat stabilizer, a slipping agent, an antistatic agent, an antiblocking agent, a filler, a viscosity modifier, a color inhibitor, etc., within the scope of not impairing the object of the present invention. These additives may be added to any layer, and multiple types may be used in combination, as long as they do not impair the effects of the present invention.
[0060] Among these, the selection of the type and amount of antioxidant is important from the viewpoint of antioxidant bleed-out. That is, such antioxidants are sterically hindered phenol-based, and at least one of them is preferably a high molecular weight type with a molecular weight of 500 or more. Specific combinations include various ones, but for example, 2,6-di-t-butyl-p-cresol (BHT: molecular weight 220.4), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene (e.g., BASF's "Irganox" (registered trademark) 1330: molecular weight 775.2), tetrakis[methylene-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane (e.g., BASF's "Irganox" (registered trademark) 1010: molecular weight 1177.7), etc. are preferably used alone or in combination.
[0061] In particular, phosphorus-based antioxidants may easily bleed out onto the surface of the biaxially oriented polypropylene film. Such bleed-out may induce various problems. For example, when a resin film is formed on the surface of the biaxially oriented polypropylene film, curing treatment of the uncured or semi-cured resin film may inhibit curing. In addition, when an electrolyte membrane or a metal membrane is formed on the surface of the biaxially oriented polypropylene film, the properties of the electrolyte membrane and the quality of the metal layer may be deteriorated. From the above viewpoint, the content of the phosphorus-based antioxidant in the biaxially oriented polypropylene film of the present invention is preferably 100 ppm or less, more preferably 50 ppm or less, and even more preferably 10 ppm or less. From the above viewpoint, it is preferable that the phosphorus-based antioxidant is not contained in the biaxially oriented polypropylene film, and the lower limit of the content is 0 ppm. Examples of phosphorus-based antioxidants include tris(2,4-di-t-butylphenyl)phosphite (e.g., BASF's "Irgafos" (registered trademark) 168: molecular weight 647). In the biaxially oriented polypropylene film, the total content of these antioxidants is preferably in the range of 0.03 to 1.0 parts by mass relative to the total amount of resin. If the amount of antioxidant is too small, the polymer may deteriorate during the extrusion process, causing the film to become discolored, or the film may have poor long-term heat resistance. If the amount of antioxidant is too large, the transparency may decrease due to the bleed-out of these antioxidants. From the above viewpoints, the content of the antioxidant is more preferably 0.05 to 0.9 parts by mass, particularly preferably 0.1 to 0.8 parts by mass, relative to the total amount of resin.
[0062] A crystal nucleating agent can be added to the biaxially stretched polypropylene film of the present invention within a range that does not interfere with the purpose. Specific examples of crystal nucleating agents include α crystal nucleating agents (dibenzylidene sorbitols, sodium benzoate, etc.), β crystal nucleating agents (potassium 1,2-hydroxystearate, magnesium benzoate, amide-based compounds such as N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide, quinacridone-based compounds, etc.). However, since excessive addition of the above-mentioned other types of nucleating agents may cause a decrease in stretchability or a decrease in transparency and strength due to void formation, etc., the amount added is 0.5 parts by mass or less, preferably 0.1 parts by mass or less, and more preferably 0.05 parts by mass or less, based on the total amount of resin.
[0063] The biaxially oriented polypropylene film of the present invention preferably does not contain organic particles and inorganic particles. The polypropylene resin that can be preferably used as the main component of the biaxially oriented polypropylene film of the present invention has low affinity with organic particles and inorganic particles, so if these particles are included, the particles may fall off during the film-forming process and contaminate the process or product. In addition, if coarse protrusions are formed on the surface of the biaxially oriented polypropylene film by particles with high hardness, when the film is used as a release film for an optical member, the unevenness may be transferred to the resin layer of the optical member. Therefore, when the film is used as a protective film or a manufacturing base film for products that require high quality, such as display members, it may cause a decrease in quality. From the above viewpoint, the polypropylene film of the present invention preferably does not contain organic particles, inorganic particles, etc.
[0064] The biaxially oriented polypropylene film of the present invention is preferably obtained by biaxially stretching an unstretched sheet obtained by using the above-mentioned resin. As the method of biaxial stretching, any of the inflation simultaneous biaxial stretching method, the tenter simultaneous biaxial stretching method, and the successive biaxial stretching method using a roll-type stretching machine and a tenter can be used. Among them, the successive biaxial stretching method using a roll-type stretching machine and a tenter is preferably adopted from the viewpoints of controlling the film formation stability, the thickness uniformity, the high rigidity and the dimensional stability of the film.
[0065] Next, one embodiment of the method for producing the biaxially oriented polypropylene film of the present invention will be described using a two-type three-layer biaxially oriented polypropylene film as an example, but the biaxially oriented polypropylene film of the present invention is not necessarily limited to this.
[0066] First, in order to improve the dispersibility of the elastomer resin or another type of polypropylene resin, it is preferable to melt-mix the polypropylene resin and the elastomer resin (or another type of polypropylene resin) in any ratio as described below to obtain a resin composition, and then pelletize the mixture.
[0067] The pellets of the resin composition obtained above are fed to a single screw extruder for the surface layer (I), and the polypropylene resin A is fed to a single screw extruder for the base layer (II). Then, melt extrusion is performed at 200 to 280°C, more preferably 220 to 275°C, and even more preferably 240 to 270°C, respectively. Then, after removing foreign matter and modified polymers with a filter installed in the middle of the polymer tube, the mixture is laminated in a layer structure of surface layer (I) / base layer (II) / surface layer (I) with a multi-manifold type composite T-die, discharged onto a casting drum, and cooled and solidified to obtain a laminated unstretched sheet having a layer structure of surface layer (I) / base layer (II) / surface layer (I). At this time, the lamination thickness ratio is preferably in the range of 1 / 4 / 1 to 1 / 60 / 1 from the viewpoint of the balance between surface properties, mechanical strength, and thermal properties. More preferably, it is 1 / 5 / 1 to 1 / 60 / 1, further preferably 1 / 10 / 1 to 1 / 60 / 1, and particularly preferably 1 / 30 / 1 to 1 / 60 / 1. By setting it within the above range, the surface layer (I) containing the elastomer resin is formed thinly and uniformly on the film surface, so that the uniformity of the height of the unevenness formed during stretching is increased, and the formation of a coarse uneven structure can be suppressed. In this case, the polypropylene resins A and B may be the same polypropylene resin.
[0068] In order to suppress the formation of β crystals during crystallization, the surface temperature of the casting drum is preferably 10 to 40°C, more preferably 15 to 30°C, even more preferably 19 to 27°C, and particularly 20 to 25°C. By setting such conditions, it becomes easy to adjust the Vmp of the A side to a suitable range. In addition, the layer structure may be a two-layer laminate structure of a surface layer (I) / base layer (II). As a method for adhering the molten resin sheet to the casting drum, any method may be used from among an electrostatic application method, an adhering method using the surface tension of water, an air knife method, a press roll method, and an underwater casting method, but the air knife method, which has good flatness and can control the surface roughness, is preferred. From the viewpoint of cooling the non-cooled drum surface of the sheet on the casting drum, it is preferable to lower the air temperature of the air knife. The air temperature of the air knife is 10 to 35°C, preferably 10 to 25°C, and even more preferably 15 to 20°C, and the blowing air speed is preferably 130 to 150 m / s. By setting such conditions, it becomes easy to adjust the number of craters on side B whose major axis exceeds 100 μm to a suitable range. In addition, it is also preferable to appropriately adjust the position of the air knife so that air flows downstream of the film formation in order to prevent vibration of the sheet. In addition, in the case of a two-type two-layer laminate structure of surface layer (I) / base layer (II), it is preferable that the surface layer (I) side is on the casting drum side.
[0069] The obtained laminated unstretched sheet is introduced into the longitudinal stretching step. In the longitudinal stretching step, it is preferable to perform longitudinal stretching in two stages in the preheating step before stretching. In the first half of the preheating step, it is preferable to heat the laminated unstretched sheet by contacting it with a plurality of metal rolls maintained at a temperature lower than the softening temperature of the elastomer resin added to the film, and the heating temperature is preferably the softening temperature of the elastomer resin -2°C or lower, more preferably the softening temperature of the elastomer resin -10°C or lower, and even more preferably the softening temperature of the elastomer resin -20°C or lower. In the second half of the preheating step, it is preferable to heat at a temperature higher than the preheating temperature of the first half of the preheating step, and the heating temperature is more preferably the preheating temperature of the first half of the preheating step +10°C or higher, and even more preferably the preheating temperature of the first half of the preheating step +20°C or higher.
[0070] The longitudinal stretching temperature is preferably the softening temperature of the elastomer resin + 15° C. or more, more preferably the softening temperature of the elastomer resin + 20° C. or more, and even more preferably the softening temperature of the elastomer resin + 25° C. or more. By setting the preheating temperature and stretching temperature within the above ranges, the elastomer resin can be appropriately softened in the preheating step and deformation can be controlled during stretching, resulting in favorable control of the surface structure of the film.
[0071] Thereafter, in the stretching step, the laminated unstretched sheet is stretched in the longitudinal direction between rolls with a difference in peripheral speed by 4.0 to 6.0 times, more preferably 4.5 to 5.8 times, and even more preferably 4.5 to 5.6 times or 4.8 to 5.5 times. The longitudinal direction refers to the direction in which the film runs during the manufacturing process (the winding direction when wound into a roll). When the stretching ratio in the longitudinal direction is 4.0 times or more, the mechanical strength in the longitudinal direction is high, so that deformation of the film is suppressed even under high tension, and the flatness of the biaxially stretched polypropylene film is easily maintained. In addition, when the stretching ratio in the longitudinal direction is 6.0 times or less, heat shrinkage caused by excessive distortion during stretching is suppressed, and the flatness of the biaxially stretched polypropylene film is easily maintained.
[0072] Next, a relaxation treatment is performed in the longitudinal direction, so that a fine uneven structure can be efficiently formed on the film surface. The temperature of the relaxation treatment in the longitudinal direction is preferably equal to or lower than the softening temperature of the elastomer resin added to the film, more preferably equal to or lower than the softening temperature of the elastomer resin minus 10°C, and even more preferably equal to or lower than the softening temperature of the elastomer resin minus 20°C, from the viewpoint of controlling the uneven surface structure and good film transportability, and the relaxation rate in the longitudinal relaxation treatment is preferably 2.0% or more and less than 10%, and the lower limit of the longitudinal relaxation treatment is more preferably 3.0%, and even more preferably 5.0%. The upper limit of the longitudinal relaxation treatment is more preferably 9.0%, and even more preferably 8.0%.
[0073] Next, the uniaxially stretched film is guided to a tenter with both ends in the width direction held by clips, preheated, and then transversely stretched 7.0 to 12 times in the width direction. The lower limit of the stretching ratio is preferably 8.0 times, more preferably 8.6 times, and even more preferably 9.0 times, from the viewpoint of uniform stretchability of the film. The upper limit of the stretching ratio is more preferably 11 times, from the viewpoint of stable stretching without film rupture. The width direction refers to the direction perpendicular to the longitudinal direction in the film plane.
[0074] From the viewpoint of uniformly stretching the film and suppressing the formation of a steep protrusion structure, the preheating temperature is preferably equal to or higher than the softening temperature of the elastomer resin added to the film and equal to or lower than the melting point of polypropylene resin A minus 15°C. The lower limit of the preheating temperature is more preferably the softening temperature of the elastomer resin + 5°C, and even more preferably the softening temperature of the elastomer resin + 10°C. The upper limit of the preheating temperature is more preferably the melting point of polypropylene resin A minus 20°C, and even more preferably the melting point of polypropylene resin A minus 25°C.
[0075] From the viewpoints of uniform stretching of the film and control of the uneven surface structure, the stretching temperature is preferably at least the softening temperature of the elastomer resin +20°C and at most the melting point of the polypropylene resin A. From the viewpoints of stable stretching without melting and breaking the film, the lower limit of the stretching temperature is more preferably the softening temperature of the elastomer resin +25°C, and even more preferably the softening temperature of the elastomer resin +30°C. The upper limit of the stretching temperature is more preferably the melting point of the polypropylene resin A -5°C, and even more preferably the melting point of the polypropylene resin A -10°C. By setting the preheating and stretching temperatures within the above ranges, the uniaxially stretched film can be uniformly stretched laterally, and a dense uneven surface structure can be formed on the surface of the biaxially stretched film.
[0076] In the subsequent heat treatment and relaxation treatment process, the film is uniformly relaxed and shrunk, and from the viewpoint of suppressing the formation of a steep protrusion structure, the film is heat-set at 140°C to 180°C, more preferably 150°C to 173°C, and even more preferably 150°C to 170°C while being tension-held at both ends in the width direction of the biaxially stretched film with clips, while being relaxed at a relaxation rate of 5.0 to 20%, more preferably 7.0 to 15%, and even more preferably 9.0 to 12% in the width direction. Furthermore, while the both ends in the width direction are tension-held with clips, the film is guided to the outside of the tenter through a cooling process at 80 to 100°C, and the clips at both ends in the width direction are released. Thereafter, the film edge portion is slit in the winder process, and a biaxially stretched polypropylene film product roll is wound up.
[0077] The biaxially oriented polypropylene film obtained as described above can be used for various industrial applications such as packaging films, cover films, process films, sanitary products, agricultural products, construction products, and medical products. However, since it has particularly excellent surface smoothness, handleability, and blocking resistance, it can be preferably used for surface protection films, support films, and release films.
[0078] Since the biaxially oriented polypropylene film of the present invention has excellent transparency, when focusing on the use of the film as a cover film, it can be particularly preferably used as a cover film for photocurable resins and dry photoresists. Here, the cover film refers to a film that is attached to an object such as a molded body or film and has the function of protecting the object from scratches, contamination, etc. that occur during processing or transportation.
[0079] The support film refers to a film used to form a film by laminating an object on the film when it is difficult to form a film from the object alone due to reasons such as the object itself being thin or fragile.
[0080] A release film is a film that has high releasability and can be attached to objects such as molded bodies and films to protect them from scratches and contamination that occur during processing and transportation, and can be easily peeled off and discarded when used as a final product.
[0081] The biaxially oriented polypropylene film of the present invention is excellent in quality and in handleability in a high-temperature environment, and therefore can be preferably used when forming a laminate with a metal film by subjecting the biaxially oriented polypropylene film of the present invention to sputtering or vapor deposition processing. That is, the biaxially oriented polypropylene film of the present invention can be made into a laminate by forming a metal film on at least one side thereof.
[0082] In sputtering and deposition, polyethylene terephthalate (PET) films, which have excellent surface smoothness, mechanical strength, heat resistance, and other properties, are often used. However, PET has high hydrophilicity due to the presence of ester bonds, and PET films contain a small amount of moisture. Such a small amount of moisture can have an adverse effect during sputtering and deposition, and the adverse effect is particularly noticeable when metals belonging to Group 1 or Group 2 of the periodic table, which are easily reactive with moisture, or compounds containing these metals are deposited. In this context, the biaxially oriented polypropylene film of the present invention can be particularly suitably used when forming a metal film containing a metal belonging to Group 1 or Group 2 of the periodic table or a compound thereof, since a laminate can be suitably obtained even in cases where it is difficult to use a PET film due to the presence of a small amount of moisture. Here, the metals belonging to Group 1 or Group 2 refer to lithium, sodium, potassium, rubidium, cesium, francium, beryllium, magnesium, calcium, strontium, barium, and radium.
[0083] In addition, under high temperature conditions, the moisture in the film evaporates as outgassing, and the effect is particularly noticeable under high vacuum conditions such as metal sputtering processes. When outgassing occurs from the film, the degree of vacuum in the system decreases, which may lead to deterioration of the quality of the metal film formed by sputtering or a decrease in the yield of sputtering. From this perspective, the biaxially oriented polypropylene film of the present invention, which has a low moisture content, can be used more suitably for applications in which a metal film is formed than a PET film with a high moisture content, and the quality of the formed metal film can also be maintained at a good level. From the above perspective, the upper limit of the moisture content of the biaxially oriented polypropylene film of the present invention is preferably 2000 ppm, more preferably 1000 ppm, and even more preferably 500 ppm. The lower limit of the moisture content is not particularly limited, but is substantially 1 ppm. The moisture content of the biaxially oriented polypropylene film can be measured by the Karl Fischer method, the details of which will be described later.
[0084] In order to set the moisture content of the biaxially stretched polypropylene film of the present invention within the above range, it is preferable to reduce the amount of hydrophilic resin or additive in the biaxially stretched polypropylene film. Specifically, the lower limit of the content of polyolefin resin such as polypropylene resin or propylene-based elastomer resin among all the constituent components of the biaxially stretched polypropylene film is preferably 90 mass%, more preferably 95 mass%, and even more preferably 97 mass%. The upper limit of the content of these resins is substantially 100 mass%. Polyolefin resins such as polypropylene resin and propylene-based elastomer resin are relatively highly hydrophobic, and by increasing the ratio of these, the moisture content of the biaxially stretched polypropylene film can be reduced.
[0085] In the biaxially stretched polypropylene film of the present invention, the total content of additives other than antioxidants (e.g., antistatic agents, viscosity modifiers, color inhibitors, slipping agents, etc.) is preferably 0 to 500 ppm or less, from the viewpoint of reducing defects due to bleed-out. Note that it is preferable to adjust the antioxidants such as phosphorus-based antioxidants as described above.
[0086] As described above, the biaxially oriented polypropylene film of the present invention has an extremely low moisture content and generates very little outgassing, and is also superior in smoothness and handling to existing olefin-based films, and is therefore preferably used when forming transparent conductive films that require stricter vacuum conditions and high quality. The transparent conductive film here refers to a thin film formed from a material that is conductive and transmits visible light, and specific examples include an indium-tin oxide (ITO) film, a zinc oxide (ZnO) film, and a palladium film.
[0087] In addition, electrolyte membranes used in fuel cells, semi-solid batteries, all-solid batteries, etc. are usually produced in an environment where temperature and humidity are strictly controlled. In particular, sulfide-type electrolyte membranes generate hydrogen sulfide when they react with moisture, so the process film used in producing the electrolyte membrane is required to have an extremely low moisture content. Therefore, the biaxially oriented polypropylene film of the present invention is preferably used for such applications.
[0088] The biaxially oriented polypropylene film of the present invention is preferably used as a current collector because of its excellent handling properties. The current collector is a foil-shaped laminate used in the electrodes of storage batteries such as lithium ion batteries, and is usually formed by laminating a metal film on a resin film as a base material. The metal film is laminated by processing such as vapor deposition, sputtering, plating, and electroless plating. In addition, from the viewpoint of increasing the energy density of the battery, the film as the base material of the current collector is required to have a small thickness, but as the film becomes thinner, its stiffness decreases, and the handling properties during processing are greatly reduced. In particular, in the process of laminating the metal film, high heat such as radiant heat is applied during processing, and tension is also applied in the conveying direction, so the film is required to have good handling properties. The biaxially oriented polypropylene film of the present invention is preferably used as a current collector because it can be made thin and has good handling properties.
[0089] The biaxially oriented polypropylene film of the present invention is preferably used as a current collector because of its excellent handling properties, and the current collector is generally used as an electrode for a storage battery. A storage battery is a device that stores electrical energy and converts it back to electrical energy when needed. Specific examples include a lead acid battery, a nickel-metal hydride battery, a lithium ion battery, a NAS battery, and a redox flow battery. EXAMPLES
[0090] The present invention will be described in detail below with reference to examples. The properties were measured and evaluated by the following methods.
[0091] (1) Film thickness The thickness was measured using a micro thickness gauge (manufactured by MITSUTOYO Co., Ltd.) A biaxially oriented polypropylene film was sampled in a 10 cm square area, and the film thickness was determined by averaging measurements taken at five random points.
[0092] (2) Peak actual volume (Vmp), valley volume (Vvv), peak density (Spd) The measurements were performed using a scanning white light interference microscope "VS1540" (Hitachi High-Tech Science Corporation, measurement conditions and device configuration will be described later), and measurements of 561.1 μm × 561.5 μm per field were performed by measuring multiple fields of view of 5 × 5 fields. Then, all images were stitched with a 20% overlap to obtain surface shape data of 2356.716 μm × 2358.294 μm. The captured image was complemented (completely complemented) using the attached analysis software, surface correction was performed using a polynomial 4th order approximation, and the surface shape was obtained by processing with a median filter (3 × 3 pixels). The measurement surfaces were both sides of the biaxially oriented polypropylene film, and the measurement positions were determined in a total of 9 positions according to the following procedure, starting from the intersection of the diagonals of the biaxially oriented polypropylene film cut into a 5 cm × 5 cm square shape. Measurements were performed at each measurement position, and Vmp, Vvv, and Spd at each measurement position were obtained according to the above procedure, and the average values were adopted as Vmp, Vvv, and Spd. In addition, Vmp on both sides is 0.1 μL / m 2 If there was a difference between the above values, the surface with the relatively smaller Vmp was designated as surface A, and the opposite surface as surface B.
[0093] <How to determine the measurement position> Measurement 1: Starting point position Measurement 2: 5.0 mm to the right of the starting point Measurement 3: 10.0 mm to the right of the starting point Measurement 4: 5.0 mm below the starting point Measurement 5: 5.0mm below and 5.0mm to the right of the starting point Measurement 6: 5.0 mm below and 10.0 mm to the right of the starting point Measurement 7: 10.0 mm below the starting point Measurement 8: 10.0 mm below and 5.0 mm to the right of the starting point Measurement 9: 10.0 mm below and 10.0 mm to the right of the starting point <Measurement conditions and equipment configuration> Objective lens: 10x Optical tube: 1x Zoom lens: 1x Wavelength filter: 530nm white Measurement mode: Wave Measurement software: VS-Measure 10.0.4.0 Analysis software: VS-Viewer 10.0.3.0 Measurement area: 561.1μm x 561.5μm Number of pixels: 1,024 x 1,024.
[0094] (3) Identification of main orientation direction and orthogonal direction to main orientation When an arbitrary direction in the film plane is set to 0°, the Young's modulus is measured in each direction that forms an angle of 0° to 175° in 5° increments with respect to the arbitrary direction, and the direction showing the highest value is the main orientation direction of the film, and the direction perpendicular to this in the film plane is the main orientation perpendicular direction of the film. The Young's modulus was measured according to the following procedure in accordance with JIS K 7161 (2014). First, a rectangular sample with a length (measurement direction) of 150 mm x width of 10 mm was cut out. A tensile test was performed using a tensile tester (Orientec "Tensilon" (registered trademark) UCT-100) in an atmosphere of room temperature 23°C and relative humidity 65%, with an initial tensile chuck distance of 50 mm and a tensile speed of 300 mm / min. The load applied to the film when the sample was elongated by 2% (when the chuck distance became 51 mm) was read, and the value divided by the cross-sectional area of the sample before the test (film thickness x 10 mm) was used as the stress F2 value at 2% elongation. Thereafter, a stress-strain curve was drawn with the elongation on the horizontal axis and the stress on the vertical axis, and the slope of the line passing through the origin and the point used to measure the F2 value was taken as Young's modulus (MPa).
[0095] (4) F5t value Five samples with a width of 10 mm and a length of 50 mm (measurement direction) were cut out from the biaxially stretched polypropylene film so that the measurement direction was the orthogonal direction to the main orientation, and marks were made at positions 15 mm from both ends to make a test length of 20 mm. Next, the rectangular samples were set in a tensile tester (Orientec's "Tensilon" (registered trademark) UCT-100) with an initial chuck distance of 20 mm, heated in an oven heated to 130 ° C for 1 minute, and then a tensile test of the film was performed at a tensile speed of 300 mm / min. The load applied to the film when the sample was 5% elongated was read, and the value divided by the cross-sectional area of the sample before the test (film thickness x width (10 mm)) was calculated as the stress (unit: MPa) at an elongation of 5%, and this value was multiplied by the film thickness calculated in (1). Measurements were performed five times for each sample, and the average value was calculated and used as the F5t value (unit: Pa · m).
[0096] (5) μd of the front and back of the film after heating at 130°C for 10 minutes A biaxially oriented polypropylene film was cut into a width of 6.5 cm and a length of 12 cm, and the test piece was sandwiched between 20 cm square pieces of paper and stacked. The test piece was heated for 10 minutes in an oven kept at 130°C under zero load, and then removed. After cooling the test piece at room temperature, it was measured at room temperature of 25°C and relative humidity of 65% using a slip tester manufactured by Toyo Seiki Co., Ltd. in accordance with JIS K 7125 (1999). The measurement was performed in the directions perpendicular to the main orientation of the biaxially oriented polypropylene film and with different surfaces overlapping each other, that is, with the main orientation perpendicular directions overlapping and the surface of one film contacting the back surface of the other film. The same measurement was performed five times for one sample, and the average value of the obtained values was calculated to be the dynamic friction coefficient (μd) of the sample.
[0097] (6) Number of craters with a major axis of 150 μm or more The measurements were performed using a scanning white light interference microscope "VS1540" (manufactured by Hitachi High-Tech Science Corporation; measurement conditions and device configuration are described later), and measurements of 561.1 μm × 561.5 μm per field were performed by measuring multiple fields of view of 5 × 5 fields. Then, all images were stitched with a 20% overlap to obtain surface shape data of 2356.716 μm × 2358.294 μm. In the hole analysis of the particle analysis mode of the attached analysis software "VS-Viewer10.0.3.0", the height threshold was set to -0.1 μm, and the number of dents with a major axis of 150 nm or more was counted. The measurements were performed on the B side of the biaxially oriented polypropylene film, and the measurement positions were determined in a total of 9 positions according to the following procedure, starting from the intersection of the diagonal lines of the biaxially oriented polypropylene film cut into a 5 cm × 5 cm square shape. Measurements were performed at each measurement position, and the number of dents at each measurement position was determined according to the above procedure, and the average value was adopted. The "method of determining the measurement position" and the "measurement conditions and device configuration" were the same as those in the previous section (2).
[0098] (7) Heat of fusion below 160°C 5 mg of biaxially oriented polypropylene film was placed in an aluminum pan as a sample and measured using a differential scanning calorimeter (Rigaku Thermoplus EVO2 DSCvesta). For the melting curve observed when the temperature was raised from 23°C to 260°C at 20°C / min (first run) under a nitrogen atmosphere, the heat flow at each temperature was corrected with a straight line that was the baseline from 60°C to 250°C, and the ratio of the heat of fusion below 160°C was calculated by subtracting the heat of fusion from 60°C to 250°C from the heat of fusion from 60°C to 160°C.
[0099] (8) Crystallization half time Using a differential scanning calorimeter (Rigaku Thermoplus EVO2 DSCvesta), 3 mg of polypropylene resin was heated from 25°C to 250°C at 20°C / min in a nitrogen atmosphere and held for 5 minutes. The temperature was then lowered from 250°C to 130°C at 20°C / min and held at 130°C for 30 minutes. The time when the sample temperature reached 130°C was defined as 0 seconds, and the elapsed time from the peak appearing after 60 seconds in the endothermic curve obtained during isothermal holding at 130°C was defined as the half crystallization time (seconds).
[0100] (9) Weight average molecular weight Mw Polypropylene resin was dissolved in 1,2,4-trichlorobenzene by stirring at 165°C for 30 minutes. After that, it was filtered using a 0.5μm filter, and the molecular weight distribution of the filtrate was measured. The weight average molecular weight Mw of the sample was calculated using a molecular weight calibration curve prepared using the following standard sample. Equipment: Agilent high temperature GPC PL-GPC220 Detector: Agilent refractive index detector (RI detector) Column: Agilent PL1110-6200 (20μm MIXED-A) x 2 ·Flow rate: 1.0mL / min Column temperature: 145℃ ·Injection volume: 0.500mL Sample concentration: 0.1wt% Standard samples: Monodisperse polystyrene manufactured by Tosoh, dibenzyl manufactured by Tokyo Kasei.
[0101] (10) Softening temperature The softening temperature was determined in accordance with JIS K 7196 (1991) using the following equipment and conditions. Using a hydraulic hot press molding machine set at 190°C, the elastomer resin was preheated for 5 minutes, press molded for 2 minutes under a pressure of 10 MPa, and then cooled at 20°C under a pressure of 10 MPa for 4 minutes to produce a sheet of a specified thickness, thereby obtaining a sheet sample. After leaving the sample at room temperature for 72 hours after molding, the sample was measured using a thermomechanical analyzer TMASS6100 (manufactured by Hitachi High-Tech Science Corporation) at a pressure of 2 kg / cm on a 1 mmφ probe. 2 The displacement (penetration depth) was measured when the specimen was heated at a temperature increase rate of 5°C / min while applying a pressure of 100 MPa. The temperature at which the displacement reached 500 µm was used as the softening temperature.
[0102] (11) Melting point Using a differential scanning calorimeter (Rigaku Thermoplus EVO2 DSCvesta), 5 mg of polypropylene resin or elastomer resin was heated in a nitrogen atmosphere from -70°C to 250°C at 20°C / min and held for 5 minutes. The temperature was then lowered from 250°C to -70°C at 20°C / min and held for 5 minutes. The temperature was then raised from -70°C to 250°C at 20°C / min. The peak temperature of the curve obtained during this temperature rise was taken as the melting point (Tm, °C).
[0103] (12) Evaluation of transfer onto substrate The biaxially oriented polypropylene film and 20 μm-thick "ZEONORFILM" (registered trademark) manufactured by Zeon Corporation were sampled into a square shape measuring 100 mm in width and 100 mm in length, and the sample was overlapped so that the side A of the biaxially oriented polypropylene film and the "ZEONORFILM" (registered trademark) were in contact with each other. The sample was then sandwiched between two acrylic plates (100 mm in width, 100 mm in length), a load of 5 kg was applied, and the sample was left to stand for 24 hours in an atmosphere at 40° C. After 24 hours, the surface of the "ZEONORFILM" (registered trademark) (the surface that was in contact with the biaxially oriented polypropylene film) was visually observed and evaluated according to the following criteria. A: It was clean and was the same as before the load was applied. B: Weak irregularities were observed. C: Strong irregularities were observed.
[0104] (13) Flatness of film when heated A corona treatment was applied to the surface of a 500 mm wide polypropylene film with a low Vmp value, and an acrylic emulsion adhesive (EX243, manufactured by E-Tech Co., Ltd.) was applied to the treated surface, which was then introduced into a drying oven at 130°C and conveyed for 60 seconds at a conveying tension of 200N to remove the solvent in the coating agent, thereby obtaining an adhesive film having an adhesive layer with a thickness of 1 μm. This adhesive film was then wound into a roll with a length of 200 m to obtain an adhesive film roll. Next, the 500 mm wide adhesive film was unwound by 1 m, and tensions of 1 kg / m and 3 kg / m were applied uniformly and evenly across the entire film width, and the presence or absence of flatness defects such as wrinkles and dents was visually confirmed. Using the obtained values, flatness evaluation was performed according to the following criteria. S: There were no areas with poor flatness when using free tension. A: With free tension, areas of poor flatness were observed, but with a tension of 1 kg / m width, no areas of poor flatness were observed. B: Poor flatness was observed at a tension of 1 kg / m width, but no poor flatness was observed at a tension of 3 kg / m width. C: Even with a tension of 3 kg / m width, areas of poor flatness were observed.
[0105] (14) Blocking resistance The biaxially oriented polypropylene film was cut to a size of 60 mm x 210 mm, and five sheets were stacked on an iron plate so that the A and B sides of the film were in contact with each other. Then, an iron plate was placed on top of the five films so that a load of 1 kgf was applied, and the films were heated in an oven set at 120°C for 15 minutes. After removing from the oven, the films were left to stand and slowly cooled to room temperature. The laminated biaxially oriented polypropylene films were then peeled off and evaluated according to the following criteria. A: The films did not adhere to each other. B: The films were in close contact with each other, but could be peeled off without rupturing. C: Impossible to peel off, or the film broke during peeling.
[0106] (15) Yield evaluation during metal film formation A magnesium oxide metal film was formed on one side of a biaxially oriented polypropylene film or a PET film by sputtering. A magnetron sputtering device was used for sputtering, and the pressure was increased from atmospheric pressure to 1×10 -5 After reducing the pressure to 2×10 -3 Magnesium oxide films were formed on the surfaces of biaxially oriented polypropylene films and PET films by sputtering at 1×10 torr. -5 The time it took to reduce the pressure to the full was measured, and the unevenness of the metal film surface was visually observed to evaluate the yield according to the following criteria, where A was considered pass and B was considered fail. A: 1×10 above atmospheric pressure -5 The time required for the pressure to be reduced to a full pressure was 50 minutes or less, and no irregularities were observed on the surface of the metal film. B: 1×10 above atmospheric pressure -5 The time to reduce the pressure to the bottom was longer than 50 minutes, or irregularities were found on the metal film surface.
[0107] (16) Moisture content A biaxially oriented polypropylene film or PET film sample was left in a room conditioned at 23°C and 20% relative humidity for at least 4 hours, and then immersed in distilled water at 23°C for 24 hours. After that, the moisture on the sample surface was wiped off, and the moisture in the sample was dried and evaporated at a temperature of 150°C using a trace moisture meter (Mitsubishi Chemical Corporation, CA-20 model), and the moisture amount was quantified by the Karl Fischer method to calculate the moisture content.
[0108] (Polypropylene resin, etc.) The resins used in the manufacture of the biaxially stretched polypropylene films of the Examples and Comparative Examples are shown in Tables 1 and 2 below. These characteristic values are values evaluated in the form of resin pellets. Seven types of polypropylene resins (PP1 to PP7) and six types of elastomer resins (ELA1 to ELA6) were prepared. Furthermore, in Examples 1 to 3, the resin composition for the surface layer (I) was prepared by melt-kneading polypropylene resin and elastomer resin in advance so as to have the mass ratio shown in Table 3. All of PP1 to PP7 contain tetrakis[methylene-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane as an antioxidant in the range of 1000 ppm to 5000 ppm, and only PP7 further contains 3000 ppm of tris(2,4-di-t-butylphenyl)phosphite. Polypropylene resin 1 (PP1): Prime Polymer Polypropylene resin 2 (PP2): Borealis Polypropylene resin 3 (PP3): Prime Polymer Polypropylene resin 4 (PP4): Made by Japan Polypropylene Corporation Polypropylene resin 5 (PP5): Idemitsu Kosan Co., Ltd. Polypropylene resin 6 (PP6): Japan Polypropylene Corporation, "WAYMAX" (registered trademark) MFX6 Polypropylene resin 7 (PP7): "WINTEC" (registered trademark) WFW4M, manufactured by Japan Polypropylene Corporation.
[0109] [Table 1]
[0110] Elastomer resin 1 (ELA1): "Toughmer" (registered trademark) PN2060, manufactured by Mitsui Chemicals, Inc. Elastomer resin 2 (ELA2): "Toughmer" (registered trademark) BL3450, manufactured by Mitsui Chemicals, Inc. Elastomer resin 3 (ELA3): "Toughmer" (registered trademark) PN2070, manufactured by Mitsui Chemicals, Inc. Elastomer resin 4 (ELA4): Japan Polypropylene Corporation, "Wintec" (registered trademark) WMG30 Elastomer resin 5 (ELA5): "Vistamaxx" (registered trademark) 3020FL, manufactured by Exxon Mobil Elastomer resin 6 (ELA6): "Welnex" (registered trademark) RFX4V, manufactured by Japan Polypropylene Corporation.
[0111] [Table 2]
[0112] In the table, MFR is a value measured in accordance with JIS K7210-1 (2014).
[0113] Example 1 Polypropylene resin 1 (PP1) and elastomer resin 1 (ELA1) were fed from a lightweight hopper to a twin-screw extruder so that the ratio was 70:30 (mass ratio), melt-kneaded at 250°C, and extruded from a die in the form of strands. The extruded resin composition was cooled and solidified in a water bath at 25°C, cut into chips, and a resin composition for the surface layer (I) was obtained. Thereafter, the resin composition for the surface layer (I) was fed to a single-screw extruder with a single screw, and PP1 was fed to a single-screw extruder with a single screw for the base layer (II) as a raw material for the base layer (II). Each resin mixture was melt-extruded at 250°C, and after removing foreign matter with a sintered filter with a 20 μm cut, the mixture was laminated in a feed block type A / B / A composite T die so that the thickness ratio of the surface layer (I) / base layer (II) / surface layer (I) was 1 / 50 / 1. The obtained molten sheet-like material was discharged onto a casting drum whose surface temperature was controlled at 20°C, and was brought into close contact with the casting drum by an air knife. Thereafter, the sheet on the casting drum was cooled by injecting compressed air at 15°C at an air speed of 140m / s by an air knife onto the non-cooled drum surface of the sheet on the casting drum, to obtain an unstretched sheet. Subsequently, the unstretched sheet was brought into contact with a metal roll at 95°C in the first half of the preheating process, and was heated to 120°C in the second half of the preheating process, and stretched 4.9 times in the longitudinal direction between rolls at 147°C with a peripheral speed difference. Next, the sheet was subjected to a 5.5% relaxation treatment in the longitudinal direction by a metal roll heated to 95°C, to obtain a uniaxially stretched film. Next, the obtained uniaxially stretched film was introduced into a tenter-type stretching machine with both ends in the width direction held by clips, preheated at 137°C for 2 seconds, stretched 9.5 times in the width direction at 152°C, and heat-treated at 155°C while giving 10% relaxation in the width direction. After a cooling process at 100°C, it was introduced to the outside of the tenter, the clips at both ends in the width direction of the film were released, and it was wound up on a core to obtain a biaxially stretched polypropylene film with a thickness of 25 μm. The physical properties and evaluation results of the obtained film are shown in Table 3.
[0114] (Examples 2 to 5, Comparative Examples 1 to 4) A biaxially stretched polypropylene film was obtained in the same manner as in Example 1, except that the raw material composition of each layer and the film-forming conditions were as shown in Table 3. In Examples 2 and 3, a resin composition obtained by melt-kneading a PP resin and an elastomer resin in advance in the same manner as in Example 1 was used for the surface layer (I) resin composition so that the mass ratio was as shown in Table 3. The thickness was adjusted by adjusting the discharge amount during extrusion and the speed of the casting drum. The physical properties and evaluation results of the obtained biaxially stretched polypropylene film are shown in Table 3.
[0115] Comparative Example 5 The raw material composition and film-forming conditions of each layer are as shown in Table 3. In the longitudinal stretching step, the unstretched sheet was preheated to 90°C with a ceramic roll, and initially stretched 1.3 times in the longitudinal direction between rolls at 90°C with a difference in peripheral speed. The film after the initial stretching was then preheated to 140°C, and the second stage of longitudinal stretching was performed at a ratio of 3.5 times. Except for this, a biaxially stretched polypropylene film was obtained in the same manner as in Example 1. At this time, the thickness was adjusted by adjusting the discharge amount during extrusion and the speed of the casting drum. The physical properties and evaluation results of the obtained biaxially stretched polypropylene film are shown in Table 3.
[0116] Comparative Example 6 Instead of the biaxially oriented polypropylene film, a PET film "Lumirror" (registered trademark) S10 (manufactured by Toray Industries, Inc.) was used to evaluate the various properties and measure the moisture content and thickness. The evaluation results are shown in Table 3.
[0117] [Table 3]
[0118] In the table, in Comparative Examples 1, 2, and 4, even on the surface where Vmp is relatively small, the 2 Since the Vmp value was not less than the above, the A side did not exist, but the value of the side with a relatively small Vmp was recorded as the A side Vmp. Note that the Vmp values of both sides were different in all examples. In addition, the moisture content and the yield during metal film production were evaluated only for Example 1, Comparative Examples 1, and 6. [Industrial Applicability]
[0119] As described above, the biaxially oriented polypropylene of the present invention can be used for various industrial applications such as packaging films, surface protection films, release films, support films, sanitary products, agricultural products, construction products, and medical products. In particular, since it has excellent quality and handleability in high-temperature environments, it can be preferably used as a release film or support film for photocurable resins, or a release film or support film for dry film resists. [Explanation of symbols]
[0120] 1: Peak actual volume Vmp 2: Load curve with height on the vertical axis and load area ratio on the horizontal axis 3: Equivalent line at area load factor of 10% 4: Valley volume Vvv 5: Equivalent line at area load ratio of 80% 6: Linear position of 100% areal load ratio
Claims
1. The peak actual volume Vmp is relatively small and is 0.1 μL / m 2 50μL / m or more 2 a layer containing an elastomer resin as a main component and comprising a polypropylene resin having a melting point of 160°C or more and 175°C or less, and which is positioned as an outermost layer on at least one of the sides, and a value F5t obtained by multiplying the stress F5 value at 5% elongation in a direction perpendicular to the main orientation of the film at 130°C by the film thickness is 50 Pa・m or more and 1000 Pa・m or less, wherein the surface having a melting point of 160°C or more and 175°C or less is defined as Side A,
2. 2. The biaxially oriented polypropylene film according to claim 1, wherein the dynamic friction coefficient μd between the front and back surfaces of the film after heating at 130° C. for 10 minutes is 0.30 or more and 1.40 or less.
3. When the surface opposite to the surface A is surface B, the surface B is 1 mm 2 The number of craters with a major axis exceeding 100 μm is 0.001 / mm 2 30 pieces / mm or more 2 The biaxially oriented polypropylene film according to any one of claims 1 to 2, wherein:
4. The peak density Spd of the A side is 1.0 peaks / mm 2 More than 100 pieces / mm 2 The biaxially oriented polypropylene film according to any one of claims 1 to 2, wherein:
5. The valley volume Vvv of the surface A is 2.0 μL / m 2 20μL / m or more 2 The biaxially oriented polypropylene film according to any one of claims 1 to 2, wherein:
6. The biaxially stretched polypropylene film according to any one of claims 1 to 2, wherein when the film is heated from 30 ° C. to 260 ° C. using a differential scanning calorimeter (DSC), the heat of fusion at 160 ° C. or less accounts for 5% to 50% of the total heat of fusion.
7. The biaxially oriented polypropylene film according to any one of claims 1 to 2, wherein the softening temperature of the elastomer resin is 70°C or higher and 150°C or lower.
8. The biaxially oriented polypropylene film according to any one of claims 1 to 2, which is used for a release film application.
9. The biaxially oriented polypropylene film according to any one of claims 1 to 2, which is used for a support film application.
Citation Information
Patent Citations
Polypropylene-based resin film
JP2008050393A
Surface protection polypropylene based resin film roll and surface protection film roll
JP2010184990A
Biaxially oriented polypropylene film
JP2015107612A
Biaxially stretched polypropylene film
WO2016051897A1
Biaxially oriented polypropylene film
WO2018147334A1